Creatine modulates cellular energy metabolism and protects against cancer cachexia-associated muscle wasting - Wei, Lulu; Wang, Ranran; Lin, Kai; Jin, Xiaolu; Li, Li; Wazir, Junaid; Pu, Wenyuan; Lian, Panpan; Lu, Renwei; Song, Shiyu; Zhao, Quan; Li, Jiabin; et al. (Frontiers in Pharmacology, 2022)
Cancer cachexia is a multifactorial syndrome defined by progressive loss of body weight with specific depletion of skeletal muscle and adipose tissue. Since there are no FDA-approved drugs that are available, nutritional intervention is recommended as a supporting therapy. Creatine supplementation has an ergogenic effect in various types of sports training, but the regulatory effects of creatine supplementation in cancer cachexia remain unknown. In this study, we investigated the impact of creatine supplementation on cachectic weight loss and muscle loss protection in a tumor-bearing cachectic mouse model, and the underlying molecular mechanism of body weight protection was further assessed. We observed decreased serum creatine levels in patients with cancer cachexia, and the creatine content in skeletal muscle was also significantly decreased in cachectic skeletal muscle in the C26 tumor-bearing mouse model. Creatine supplementation protected against cancer cachexia-associated body weight loss and muscle wasting and induced greater improvements in grip strength. Mechanistically, creatine treatment altered the dysfunction and morphological abnormalities of mitochondria, thus protecting against cachectic muscle wasting by inhibiting the abnormal overactivation of the ubiquitin-proteasome system (UPS) and autophagic lysosomal system (ALS). In addition, electron microscopy revealed that creatine supplementation alleviated the observed increase in the percentage of damaged mitochondria in C26 mice, indicating that nutritional intervention with creatine supplementation effectively counteracts mitochondrial dysfunction to mitigate muscle loss in cancer cachexia. These results uncover a previously uncharacterized role for creatine in cachectic muscle wasting by modulating cellular energy metabolism to reduce the level of muscle cell atrophy.